Extensions of Ostrowski Type Inequalities via h-Integrals and s-Convexity. (11th November 2021) - Khan, Khuram Ali; Awan, Khalid Mahmood; Ditta, Allah; Nosheen, Ammara; Matendo, Rostin Mabela
Abstract : In this paper, Hölder, Minkowski, and power mean inequalities are used to establish Ostrowski type inequalities for s -convex functions via h -calculus. The new inequalities are generalized versions of Ostrowski type inequalities available in literature.